Avian Research - Zheng, Guangmei
Avian Research is an open access, peer-reviewed journal publishing high quality research and review articles on all aspects of ornithology from all over the world. It aims to report the latest and most significant progress in ornithology and to encourage exchange of ideas among international ornithologists. As an open access journal, Avian Research provides a unique opportunity to publish high quality contents that will be internationally accessible to any reader at no cost.